Review paperThe role of genetic factors in the pathogenesis of neonatal intraventricular hemorrhage - Szpecht, Dawid; Szymankiewicz, Marta; Seremak-Mrozikiewicz, Agnieszka; Gadzinowski, Janusz (Folia Neuropathologica, 2015)
Intraventricular hemorrhage (IVH) affects 15-20% of babies born before 32 weeks of pregnancy. Besides gestational age (below 32 weeks) there are a number of IVH risk factors. Increasing attention is being paid to genetic factors in the development of IVH. The authors discuss genetic factors (mutations of coagulation factors, gene polymorphisms in pro-inflammatory cytokines, mutation of type IV collagen gene, polymorphisms of genes responsible for the regulation of systemic blood pressure and cerebral blood flows) whose involvement in IVH pathogenesis has been confirmed in the highest number of reports and for which being a carrier plays an important role in their pathophysiology. The role of genetic factors in IVH remains unclear. Further analysis of the role of genetic factors in the pathophysiology of IVH will make it possible to determine the group of newborns who are specifically at risk of developing IVH in the perinatal period.